The influence of dust aerosols on solar radiation and near-surface temperature during a severe duststorm transport episode - Huang, Guan; Zhou, Yaman; Guo, Zijia; Liu, Xin; Chen, Yonghang; Liu, Qiong; Ta, Zhijie; Wang, Pengtao; He, Qing; Gao, Jiacheng; Zhang, Ying (Frontiers in Environmental Science, 2023)
In the west of China, a rarely seen black storm, with a high intensity of dust aerosols and a large area of influence occurred on April 26-29, 2015 for the first time, after more than 30 years. Based on the regional climate model (RegCM version 4.6), combined with Moderate Resolution Imaging Spectroradiometer (MODIS) satellite retrieval, meteorological and environmental data, this work presented the pollution situation, weather background, and airflow trajectory during the black storm episode. Besides, we analyzed the temporal-spatial distribution of Aerosol Optical Depth (AOD) as well as the impacts of dust aerosols on solar radiation and near-surface temperature under this extreme weather condition. We discovered this episode was caused by the surface cold high pressure and frontal transit under the background of the upper-air circulation of "two troughs and two ridges". The pollutants primarily from Xinjiang and the Central Asia region along with the airflow entered northern Xinjiang almost simultaneously, piled up along the Tianshan Mountains, and then crossed the mountains into southern Xinjiang. Besides, the areas with high AOD were mostly in the desert regions and basins, whereas the low-value areas were mountainous areas with relatively high altitudes due to the effect of geographical and climatic conditions. The AOD from RegCM4.6 was generally lower, unlike the MODIS AOD. Moreover, the dust aerosols from this black storm caused a significant decline in net short-wave radiation (NSR) both at the top of the atmosphere (TOA) and surface. The cooling effect was more significant in the region with high AOD, for the areas where the AOD was higher than 0.7, the net short-wave radiative forcing of dust aerosols (ADRF) at the surface was above -70 W•m−2; on the other hand, the cooling effect at the TOA was not as significant as that at the surface, with the ADRFTOA being only about a quarter of the ADRFSUR. The ADRFSUR could reduce the near-surface temperature, and the region with a large temperature drop corresponded to the high-value areas of ADRFSUR/AOD. During this black storm, the near-surface temperature response to dust aerosols reached 0.4-2.9℃ with a significant temperature drop because of cold air.